Self-rated health and mortality in individuals with diabetes mellitus: prospective cohort study. Issue 1 (15th February 2012) - Wennberg, Patrik; Rolandsson, Olov; Jerdén, Lars; Boeing, Heiner; Sluik, Diewertje; Kaaks, Rudolf; Teucher, Birgit; Spijkerman, Annemieke; de Mesquita, Bas Bueno; Dethlefsen, Claus; Nilsson, Peter; Nöthlings, Ute
Abstract : Objectives: To investigate whether low self-rated health (SRH) is associated with increased mortality in individuals with diabetes. Design: Population-based prospective cohort study. Setting: Enrolment took place between 1992 and 2000 in four centres (Bilthoven, Heidelberg, Potsdam, Umeå) in a subcohort nested in the European Prospective Investigation into Cancer and Nutrition. Participants: 3257 individuals (mean ± SD age was 55.8±7.6 years and 42% women) with confirmed diagnosis of diabetes mellitus. Primary outcome measure: The authors used Cox proportional hazards modelling to estimate HRs for total mortality controlling for age, centre, sex, educational level, body mass index, physical inactivity, smoking, insulin treatment, hypertension, hyperlipidaemia and history of myocardial infarction, stroke or cancer. Results: During follow-up (mean follow-up ± SD was 8.6±2.3 years), 344 deaths (241 men/103 women) occurred. In a multivariate model, individuals with low SRH were at higher risk of mortality (HR 1.38, 95% CI 1.10 to 1.73) than those with high SRH. The association was mainly driven by increased 5-year mortality and was stronger among individuals with body mass index of <25 kg/m 2 than among obese individuals. In sex-specific analyses, the association was statistically significant in men only. There was no indication of heterogeneity across centres. Conclusions: Low SRH was associated with increased mortality in individuals with diabetes after controlling for established risk factors. In patients with diabetes with low SRH, the physician should consider a more detailed consultation and intensified support.